Efectos de la música infantil en la expresión corporal en niños de la institución educativa inicial N°333, Cushillo Cocha 2024 - Guerrero Witancort, Keny (2025)
The objective of this research was to determine the effect of children's music on the body expression of the children of the Institution Educative Initial N°333 Cushillo Cocha, 2024. A quantitative approach was used with a quasi-experimental design. The population was made up of 84 children aged 4 and 5 years, selecting a stratified probabilistic sample of 50% (42 children), divided into an experimental group (21) and a control group (21). Data collection was carried out through observation, using a guide validated by experts and whose reliability was determined using Cronbach's Alpha test. The results obtained through the Student t test for independent samples (t = 6.322, p = 0.000) indicated a statistically significant difference between both groups. It is concluded that the application of children's music had a positive effect on the development of body expression in the participating children.